Vestibular schwannoma associated with neurofibromatosis type 2: Clinical course following stereotactic radiosurgery - Kim, Junhyung; Byeon, Yukyeng; Song, Sang Woo; Cho, Young Hyun; Hong, Chang-Ki; Hong, Seok Ho; Kim, Jeong Hoon; Lee, Do Heui; Park, Ji Eun; Kim, Ho Sung; Kim, Young-Hoon (Frontiers in Oncology, 2022)
Objective: A lack of understanding of the clinical course of neurofibromatosis type 2 (NF2)-associated vestibular schwannoma (VS) often complicates the decision-making in terms of optimal timing and mode of treatment. We investigated the outcomes of stereotactic radiosurgery (SRS) in these cases. Methods: We retrospectively analyzed NF2 patients treated with Gamma-Knife SRS for VS in our tertiary referral center. A total of 41 treated lesions from 33 patients were collected with a follow-up period of 69.1 (45.0-104.8) months. We reviewed the treatment history, hearing function, and other tumor or treatment-related morbidities in individual cases. We also analyzed pre- and post-treatment tumor volumes via imaging studies. Longitudinal volumetric analyses were conducted for the tumor volume response of the 41 treated lesions following SRS. The growth pattern of 22 unirradiated lesions during an observation period of 83.4 (61.1-120.4) months was separately evaluated. Results: Most treated lesions showed effective tumor control up to 85% at 60 months after SRS, whereas unirradiated lesions progressed with a relative volume increase of 14.0% (7.8-27.0) per year during the observation period. Twelve (29%) cases showed pseudoprogression with significant volume expansion in the early follow-up period, which reduced the actual rate of tumor control to 57% at 24 months. Among the patients with serviceable hearing, two (20%) cases lost the hearing function on the treated side during the early follow-up period within 24 months. Conclusions: Progressive NF2-associated VS can be adequately controlled by SRS but the short-term effects of this treatment are not very advantageous in terms of preserving hearing function. SRS treatment candidates should therefore be carefully selected.